2014
DOI: 10.1016/j.molmet.2013.12.006
|View full text |Cite
|
Sign up to set email alerts
|

AVP neurons in the paraventricular nucleus of the hypothalamus regulate feeding

Abstract: Melanocortins and their receptors are critical components of energy homeostasis and the paraventricular nucleus of the hypothalamus (PVH) is an important site of melanocortin action. Although best known for its role in osmoregulation, arginine vasopressin (AVP) has been implicated in feeding and is robustly expressed in the PVH. Since the anorectic melanocortin agonist MTII activates PVH-AVP neurons, we hypothesized that PVH-AVP neurons contribute to PVH-mediated anorexia. To test this, we used an AVP-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 25 publications
3
84
1
Order By: Relevance
“…Using multiple anatomical tracing techniques in Avp ires−Cre/+ mice (Pei et al, 2014), we confirmed that mouse VP pp neurons exhibited similar anatomical properties and that SON VP pp neurons did not send substantial collaterals to other brain areas (see Figure 1A, Figure S1, and Experimental Procedures).…”
Section: Resultssupporting
confidence: 52%
“…Using multiple anatomical tracing techniques in Avp ires−Cre/+ mice (Pei et al, 2014), we confirmed that mouse VP pp neurons exhibited similar anatomical properties and that SON VP pp neurons did not send substantial collaterals to other brain areas (see Figure 1A, Figure S1, and Experimental Procedures).…”
Section: Resultssupporting
confidence: 52%
“…Therefore, an osmotic effect is unlikely to underlie the response of vasopressin or oxytocin neurones to SCM ingestion in our experiments. There is little evidence for a role of vasopressin neurones in appetite control (43,44). The mechanisms underlying a potential role of vasopressin in appetite control remains unknown; unlike oxytocin neurones, SON vasopressin neurones do not appear to be innervated by NTS projections and are inhibited by the satiety signal CCK (28).…”
Section: Discussionmentioning
confidence: 99%
“…The PVHpml predominantly contains oxytocin and vasopressin neurons (Simmons and Swanson, 2009). This is particularly interesting given that manipulations of either peptide interfere with the control of feeding behavior (e.g., Pei et al, 2014; see Olszewski et al, 2010 for review), and both are important for other forms of learning (Lahoud and Maroun, 2013; see Engelmann et al, 1996 for review). Our current findings that PVHpml neurons are recruited during tone-food learning indicate a potential role for PVH oxytocin and/or vasopressin function in appetitive associative learning and memory.…”
Section: Discussionmentioning
confidence: 99%